Formação de professores sobre o campo conceitual multiplicativo: referenciais teóricos em pesquisas - Alencar, Edvonete Souza de (2016)
This research aims to investigate the theoretical frameworks that support Brazilian research published between 1997-2015, regarding the training of teachers in the early elementary years on the Multiplicative Conceptual Field. In order to achieve it, research review procedures called qualitative metasynthesis was used. The search of the investigation was carried out on the website of Capes Bank of Theses using the expressions "Teacher Training" and "Multiplicative Conceptual Field" in addition to the use of a filter for investigations that would discourse on "Continuing Education" and "Early ElementaryYears". A group of research in which we seek the most used theoretical frameworks was selected; Shulman and Vergnaud were found. A new selection was carried out, focusing on the research which had presented both authors as references. With this smaller group of research, a qualitative metasynthesis was held regarding the use of these theoretical references for the investigations. The qualitative metasynthesis was performed presenting categories which were taken from these reports, in which similarities were observed as well as differences and complementarities of the most discussed theoretical frameworks. In general, the use of the qualitative metasynthesis of the studies concerning Shulman through the investigations made it possible to identify that these investigations used the three categories of knowledge as those presented by Shulman (specific, pedagogical and curricular). It is worth mentioning that there were not any differences observed in relation to what is mentioned by the author. However, it was pointed out some aspects which were addressed by some research that complement Shulman studies regarding the specific and pedagogical knowledge used to encourage reflection on teacher training. The qualitative metasynthesis of the use of Vergnaud's theory by research has shown similarities in terms of approaches on the explanation of the Theory of Conceptual Fields. It was observed that most of the investigations focus on explaining what characterizes the Theory of Vergnaud. It was found that three of the selected research deepen their explanations of the Multiplicative Conceptual Field and that such investigations do not show different aspects of what is proposed by Vergnaud. In addition to that, it was stated that one of the research complements Vergnaud studies when explaining relational and numerical calculations in the Multiplicative Conceptual Field. This thesis led us to infer the need to conduct more studies on this topic and to reflect on the use of theoretical frameworks applied by the investigations